Cultural Ecology of the Highland Communities: Some Anthropological Observations from Eastern Nepal - Uprety, Laya Prasad (Dhaulagiri Journal of Sociology and Anthropology, 2006)
This research paper has two-fold objectives: (i) to familiarize the graduate students majoring in anthropology with the theoretical underpinnings of cultural ecology, and (ii) to analyze and explicate the ecological-cultural adaptations among the communities living in the harsh mountain ecological setting of eastern Nepal and their traditional organizations and institutions contributing to community welfare and social equity within the framework of cultural ecology. The paper has been based on the impressionistic data garnered in from the Himalayan ecological setting in eastern Nepal. DOI: 10.3126/dsaj.v1i0.273 Dhaulagiri Vol.1 (2005) pp.1-32